A new species of Lepanthes (Pleurothallidinae) in honour "Bachué", the mythological mother of the indigenous Muisca people - Parra Sánchez, Edicson
During an expedition in which we randomly placed 341 plots across a large elevation range (1100-3880 m) and spatial gradient (~270 km) in the Eastern Cordillera, we found a new species of the genus Lepan-thes in Santuario de Fauna y Flora de Iguaque, Boyaca, Colombia. We propose L. bachue as a new species that is most similar to L. papallactae but it differs in its proliferous plants (vs. non proliferous), the petals with the upper lobe 2.5 mm long, the lower lobe 4.5 mm long, larger than the upper one, and the margins fimbriate (vs. lobes subequal, 4.5 mm long and shortly pubescent) and the lip with the blades oblong, sub-sigmoid, adnate to the middle of the column with a short oblong, bifid, an appendix hiding in the middle (vs. blades narrowly elliptical-oblong, adnate to the column above the middle with a recurved pedunculate, biglandular appendix). Our extensive sampling across different areas suggests that this species is geographically restricted and highly specialized in terms of habitat. Thus, it is urgent to protect its natural habitat and population.